Impact of Fiscal and Financial Dynamics on Shaping the Development in Nepal - Adhikari, Padma Kumar; Dangal, Dil Nath; Gajurel, Ram Prasad; Ghimire, Krishna Prasad (Journal of Development and Administrative Studies, 2023)
This study attempts to explore the fiscal and financial dynamics of the economic development in Nepal. Employing robust ordinary least squares (OLS) with time series spanning from 1993 to 2022, this study examined the long-run impact of various fiscal and financial variables on Nepal's GDP. Before it, this study pretested cointegration between studied variables and failed to find any evidence of such a long relationship. Thus, the findings of OLS indicated that value-added tax (VAT) and investment significantly drive GDP growth, while income tax and remittances have no significant impact on GDP in Nepal. The study thus suggests that policymakers should focus on proper channelization of income tax and remittance inflows with VAT and investment for the economic development of Nepal.